Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 1:
\(S=\frac{10}{7}+\frac{10}{7^2}+\frac{10}{7^3}+...+\frac{10}{7^{10}}\)
\(\frac{1}{7}S=\frac{10}{7^2}+\frac{10}{7^3}+....+\frac{10}{7^{11}}\)
\(\rightarrow\)\(\left(1-\frac{1}{7}\right).S=\frac{10}{7}-\frac{10}{7^{11}}\)
=> \(S=\frac{10.7^{10}-10}{7^{10}.6}\)
b, \(\frac{2^{10}\left(13+65\right)}{2^8.104}\)
=\(\frac{2^2.78}{104}\)=\(\frac{312}{104}\)=3
a) \(\frac{24-x}{16^5}=32^6\)
=> 24 - x = 326.165
<=> 24 - x = (25)6 . (24)5
<=> 24 - x = 230 . 220
<=> 24 - x = 250
<=> x = 24 - 250
b) (-2)x = -46.85
<=> (-2)x = -(22)6.(23)5
<=> (-2)x = -212.215
<=> (-2)x = -227
<=> (-2)x = (-2)27
<=> x = 27
Vậy x = 27
d) \(2^x=\frac{2^8}{4^4}\)
<=> \(2^x=\frac{2^8}{\left(2^2\right)^4}\)
<=> \(2^x=\frac{2^8}{2^8}\)
<=> 2x = 1 <=> x = 0
a.
\(\frac{24-x}{16^5}=32^6\)
( 24 - x ) : 165 = 326
24 - x = 326 . 165
24 - x = ( 16 )2.6 . 165
24 - x = 1612 . 165
24 - x = 1612 + 5
24 - x = 1617
x = 24 - 1617
Vậy x = 24 - 1617
b.
( - 2 )x = - 46 . 85
( - 2 )x = - 46 . ( - 4 ) - 2 . 5
( - 2 )x = - 46 . ( - 4 )- 10
( - 2 )x = - 4 6 + ( - 10 )
( - 2 )x = - 4-4
( - 2 )x = ( - 2 )-2 . ( - 4 )
( - 2 )x = ( - 2 )8
=> x = 8
Vậy x = 8
\(a)15\frac{3}{13}-\left(3\frac{4}{7}+8\frac{3}{13}\right)\)
\(=15\frac{3}{13}-3\frac{4}{7}-8\frac{3}{13}\)
\(=15\frac{3}{13}-8\frac{3}{13}-3\frac{4}{7}\)
\(=7-3\frac{4}{7}\)
\(=6\frac{7}{7}-3\frac{4}{7}=3\frac{3}{7}\)
\(b)\left(7\frac{4}{9}+4\frac{7}{11}\right)-3\frac{4}{9}\)
\(=7\frac{4}{9}-4\frac{7}{11}-3\frac{4}{9}\)
\(=7\frac{4}{9}-3\frac{4}{9}-4\frac{7}{11}\)
\(=4-4\frac{7}{11}=\frac{7}{11}\)
Bạn ấy lm câu a rùi mik lm 3 câu còn lại nha
\(27^{16}:9^{10}\)
\(=3^{16}\cdot9^{16}:9^{10}\)
\(=9^8\cdot9^6=9^{14}\)
\(125^3:25^4\)
\(=5^3\cdot25^3:25^4\)
\(=5\cdot25\cdot25^3:25^4\)
\(=5\cdot25^4:25^4\)
\(=5\cdot1=5\)
\(24^4:3^4-32^{12}:16^{12}\)
\(=8^4\cdot3^4:3^4-2^{12}\cdot16^{12}:16^{12}\)
\(=8^4-2^{12}\)
\(=4096-4096\)
\(=0\)
Ta có :\(\frac{2^{13}+32}{2^{10}+4}=\frac{2^{13}+2^5}{2^{10}+2^2}=\frac{2^5\left(2^8+1\right)}{2^2\left(2^8+1\right)}=\frac{2^5}{2^2}=2^3=8\)
\(\frac{2^{13}+32}{2^{10}+4}\)
\(=\frac{2^5.\left(2^8+1\right)}{2^2.\left(2^8+1\right)}\)
\(=2^3\)
\(=8\)